INTERNASIONALISASI PENDIDIKAN TINGGI ISLAM MELALUI REALISASI THE GLOBAL GOALS BERBASIS MAQASHID SYARIAH - Rosidin, Rosidin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
The era of globalization is characterized by a shift in the concept of citizenship. From nation citizenship to global one. The implication is the need to reform Islamic education based on global standardization and Islamic values. The concrete form is the internationalization of Islamic education through the realization of the global goals based on maqashid sharia. The model established is the education that makes maqashid sharia as the core curriculum (model of comprehensive education), open to all parties to obtain or provide educational (emancipatory), ready to compete in the global competition (competitive), to cultivate the attitude of flexibility and open-minded towards each other (inclusive), cooperate with global citizens (collaborative) and is able to bring actual change for the community (transformative).